A Hybrid CPT System Using Quadrature Double Horizontal Capacitive Couplers for High-Misalignment Tolerance and Constant Voltage Output - Chen, Ting; Ma, Zhihui; Xu, Zhicheng; Wang, Fengxian; Zhang, Xian; Li, Guangyao; Zhao, Xuan; Wang, Yuqiao (IEEE transactions on power electronics, 2025)
In capacitive power transfer (CPT) systems, coupling variations are inevitable due to air gap changes and misalignment between transmitting and receiving plates, which hinders constant output and optimal efficiency. This paper proposes a hybrid CPT system using quadrature double horizontal capacitive couplers (QDHCC) for high-misalignment tolerance and constant voltage (CV) output. The system employs a hybrid compensation topology that combines LCLC-LC and LC-LCLC compensation topologies, based on structure of input-parallel-output-series (IPOS). QDHCC serve as the power transfer channels, achieving decoupling as the coupler moves along the X, Y, and Z axes. This design mitigates complex cross-couplings and ensures independence between the two power transfer channels. A tripleeffect multi-objective optimization method for compensation circuit parameters is proposed to further enhance the system's tolerance to misalignment, reduce the voltage stress on the coupler and improve system efficiency. The constant voltage output within predetermined misalignment distance is obtained. The alignment tolerance for adjustments along the X-axis and Y-axis is 40%, while it reaches 100% for the Z-axis. Finally, experimental results demonstrated the effectiveness of the proposed scheme with a maximum efficiency of 87.5%.